On CALL: One Approach to Improving Services for Students With Low-Incidence Disabilities. (September 2015) - Bradley-Johnson, Sharon; Johnson, C. Merle; Drevon, Daniel D.
Students with low-incidence disabilities frequently receive less than optimal psychoeducational services because the specialized tests and instructional materials required to meet their idiosyncratic needs often are unavailable due to budget constraints, inadequate training of school personnel, and the difficulty school personnel have keeping current on low-incidence disabilities. To enhance the services provided for these students, a centralized statewide lending library for school personnel serving students with low-incidence disabilities was implemented. The development of this project, its impact, and the needs of school personnel in the area of low-incidence disabilities are described.